What happens when the insecticide does not kill? A review of sublethal toxicology and insecticide resistance in triatomines - Mougabure Cueto, Gastón Adolfo (2024)
Chagas disease is considered one of the most important human parasitosis in America. This disease is mainly transmitted by insects of the subfamily Triatominae. The chemical vector control is the main tool for reducing the incidence of the disease. However, the presence of triatomines after pyrethroids spraying has been reported in some regions, as in the case of Triatoma infestans in Argentina and Bolivia. The presence of insects can be explained by the colonization from neighbouring areas, the reduction of insecticide dose to sublethal levels due to environmental factors, and/or by the evolution of insecticide resistance. In the last two scenarios, a proportion of the insects is not killed by insecticide and gives rise to residual populations. This article focuses on the toxicological processes associated with these scenarios in triatomines. Sublethal doses may have different effects on insect biology, that is, sublethal effects, which may contribute to the control. In addition, for insect disease vectors, sublethal doses could have negative effectson disease transmission. The study of sublethal effects in triatomines has focused primarilyon the sequence of symptoms associated with nervous intoxication. However, the effectsof sublethal doses on excretion, reproduction and morphology have also been studied.Rhodnius prolixus and T. infestans and pyrethroids insecticides were the triatomine speciesand insecticides, respectively, mainly studied. Insecticide resistance is an evolutionary phenomenon in which the insecticide acts as a selective force, concentrating on the insectpopulation’s pre-existing traits that confer resistance. This leads to a reduction in the susceptibilityto the insecticide, which was previously effective in controlling this species. The evolution of resistance in triatomines received little attention before the 2000s, but after the detection of the first focus of resistance associated with chemical control failures in T. infestans from Argentina in 2002, the study of resistance increased remarkably. A significant number of works have studied the geographical distribution, the resistance mechanisms, the biological modifications associated with resistance, the environmental influences and the genetic of T. infestans resistant to pyrethroid insecticides. Currently, studies of insecticide resistance are gradually being extended to other areas and other species. The aim of this article was to review the knowledge on both phenomena (sublethal effects and insecticide resistance) in triatomines. For a better understanding of this article, some concepts and processes related to insect-insecticide interactions, individual and population toxicology and evolutionary biology are briefly reviewed. Finally, possible futurelines of research in triatomine toxicology are discussed.